Exercise-Associated Changes in Body Composition and Metabolic Biomarkers Following an Eight-Week Submaximal Exercise Program in Women Across Different BMI Categories and with Type 2 Diabetes - Buru, Kivanc; Cinar, Vedat; Akbulut, Taner; Aslan, Mehdi; Orgun, Meva Ceren; Cinar, Fidan; Lee, Do-Youn (Mdpi, 2026)
Background/Objectives: This study evaluated exercise-induced changes in body composition and metabolic biomarkers in women across distinct BMI categories and individuals with Type 2 diabetes. Methods: In this quasi-experimental study, 40 sedentary women were stratified into five groups (n = 8): underweight, normal weight, overweight, obese, and T2DM. The rigorous eight-week supervised program utilized submaximal exercise at 70-85% heart rate reserve, calculated via the Karvonen method and monitored by telemetry. Assessments included anthropometric parameters (BMI, fat mass, visceral fat) and serum biomarkers (irisin, myonectin, HIF-1 alpha, insulin, glucose). Fasting venous samples were collected at baseline and 72 h post-intervention to minimize acute effects, then analyzed using validated ELISA protocols. Statistical data were evaluated using parametric or non-parametric tests with significance set at p < 0.05. Results: Post-intervention, significant reductions in weight, fat mass, and visceral fat occurred in overweight, obese, and T2DM groups (p < 0.05). Muscle mass increased across all cohorts. Fasting insulin and glucose decreased significantly in all except the underweight group, with the most pronounced improvements in T2DM and obese participants. Serum irisin increased significantly across all groups (p < 0.05), indicating a universal exercise-induced myokine response. Conversely, myonectin levels decreased significantly only in the normal-weight group, while HIF-1 alpha increased specifically in the T2DM cohort. These findings suggest that baseline BMI and metabolic status are critical determinants of exercise responsiveness, leading to heterogeneous biomarker patterns despite consistent improvements in body composition and basic glycemic regulation. Conclusions: An eight-week submaximal program effectively improves body composition and glycemic regulation, though specific biomarker responses are highly dependent on baseline BMI and metabolic status.
Keywords: type 2 diabetes mellitus; submaximal exercise; irisin; myonectin; HIF-1 alpha; insulin resistance; metabolic biomarkers